Challenges to the Emergence of Telerehabilitation in a Developing Country: A Systematic Review - Leochico, Carl Froilan D.; Espiritu, Adrian I.; Ignacio, Sharon D.; Mojica, Jose Alvin P. (Frontiers in Neurology, 2020)
Background: Despite being known abroad as a viable alternative to face-to-face consultation and therapy, telerehabilitation has not fully emerged in developing countries like the Philippines. In the midst of coronavirus disease 2019 (COVID-19) pandemic, wherein social distancing disrupted the in-clinic delivery of rehabilitation services, Filipinos attempted to explore telerehabilitation. However, several hindrances were observed especially during the pre-implementation phase of telerehabilitation, necessitating a review of existing local evidences. Objective: We aimed to determine the challenges faced by telerehabilitation in the Philippines. Method: We searched until March 2020 through Pubmed, Scopus, Embase, Cochrane Library and HeRDIN for telerehabilitation-related publications wherein Filipinos were involved as investigator or population. Because of hypothesized low number of scientific outputs on telerehabilitation locally, we performed handsearching through grey literature and included relevant papers from different rehabilitation-related professional organizations in the Philippines. We analyzed the papers and extracted the human, organizational and technical challenges to telerehabilitation or telehealth in general. Results: We analyzed 21 published and 4 unpublished papers, which were mostly reviews (8), feasibility studies (6), or case reports/ series (4). Twelve out of 25 studies engaged patients and physicians in remote teleconsultation, teletherapy, telementoring, or telemonitoring. Patients sought telemedicine or telerehabilitation for general medical conditions (in 3 studies), chronic diseases (2), mental health issues (2), orthopedic problems (2), neurologic conditions (1), communication disorders (1), and cardiac conditions (1). Outcomes in aforementioned studies mostly included telehealth acceptance, facilitators, barriers, and satisfaction. Other studies were related to telehealth governance, legalities, and ethical issues. We identified 18 human, 17 organizational and 18 technical unique challenges related to telerehabilitation in the Philippines. The most common challenges were slow internet speed (in 10 studies), legal concerns (9), and skepticism (9). Conclusion: There is paucity of data on telerehabilitation in the Philippines. Local efforts can focus on exploring or addressing the most pressing human, organizational and technical challenges to the emergence of telerehabilitation in the country.